(x+7)(x+9)=2x+62

Simple and best practice solution for (x+7)(x+9)=2x+62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+7)(x+9)=2x+62 equation:


Simplifying
(x + 7)(x + 9) = 2x + 62

Reorder the terms:
(7 + x)(x + 9) = 2x + 62

Reorder the terms:
(7 + x)(9 + x) = 2x + 62

Multiply (7 + x) * (9 + x)
(7(9 + x) + x(9 + x)) = 2x + 62
((9 * 7 + x * 7) + x(9 + x)) = 2x + 62
((63 + 7x) + x(9 + x)) = 2x + 62
(63 + 7x + (9 * x + x * x)) = 2x + 62
(63 + 7x + (9x + x2)) = 2x + 62

Combine like terms: 7x + 9x = 16x
(63 + 16x + x2) = 2x + 62

Reorder the terms:
63 + 16x + x2 = 62 + 2x

Solving
63 + 16x + x2 = 62 + 2x

Solving for variable 'x'.

Reorder the terms:
63 + -62 + 16x + -2x + x2 = 62 + 2x + -62 + -2x

Combine like terms: 63 + -62 = 1
1 + 16x + -2x + x2 = 62 + 2x + -62 + -2x

Combine like terms: 16x + -2x = 14x
1 + 14x + x2 = 62 + 2x + -62 + -2x

Reorder the terms:
1 + 14x + x2 = 62 + -62 + 2x + -2x

Combine like terms: 62 + -62 = 0
1 + 14x + x2 = 0 + 2x + -2x
1 + 14x + x2 = 2x + -2x

Combine like terms: 2x + -2x = 0
1 + 14x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-1' to each side of the equation.
1 + 14x + -1 + x2 = 0 + -1

Reorder the terms:
1 + -1 + 14x + x2 = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 14x + x2 = 0 + -1
14x + x2 = 0 + -1

Combine like terms: 0 + -1 = -1
14x + x2 = -1

The x term is 14x.  Take half its coefficient (7).
Square it (49) and add it to both sides.

Add '49' to each side of the equation.
14x + 49 + x2 = -1 + 49

Reorder the terms:
49 + 14x + x2 = -1 + 49

Combine like terms: -1 + 49 = 48
49 + 14x + x2 = 48

Factor a perfect square on the left side:
(x + 7)(x + 7) = 48

Calculate the square root of the right side: 6.92820323

Break this problem into two subproblems by setting 
(x + 7) equal to 6.92820323 and -6.92820323.

Subproblem 1

x + 7 = 6.92820323 Simplifying x + 7 = 6.92820323 Reorder the terms: 7 + x = 6.92820323 Solving 7 + x = 6.92820323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 6.92820323 + -7 Combine like terms: 7 + -7 = 0 0 + x = 6.92820323 + -7 x = 6.92820323 + -7 Combine like terms: 6.92820323 + -7 = -0.07179677 x = -0.07179677 Simplifying x = -0.07179677

Subproblem 2

x + 7 = -6.92820323 Simplifying x + 7 = -6.92820323 Reorder the terms: 7 + x = -6.92820323 Solving 7 + x = -6.92820323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = -6.92820323 + -7 Combine like terms: 7 + -7 = 0 0 + x = -6.92820323 + -7 x = -6.92820323 + -7 Combine like terms: -6.92820323 + -7 = -13.92820323 x = -13.92820323 Simplifying x = -13.92820323

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.07179677, -13.92820323}

See similar equations:

| 20x^3-6x=0 | | (x+2)*x=80 | | 4x^2-y^2-40x-14y+15=0 | | 2x+3-4=2x-1 | | 81-3x=24x+18 | | -69-9x=9x+21 | | 122-5x=4x+15 | | 0=-2x-4 | | 6n+18=6 | | (x+2)*x=8 | | (D^3+4D^2-3D-18)y=0 | | 0.4x+4.5=0.3x+2.5 | | 6a-6+4a=4a+24 | | p+6.5p=27 | | -12=6x-8x-22 | | 7(3-0.5k)=3k-5 | | .625y-7=3 | | 5(5-12)-24=3(s+2) | | -2x-y=10 | | -5.6x=-19.04 | | x(3x-1)=x^2+15 | | 6x-15y=60 | | 7x+3=5x+12 | | 3x^2-x^2-x=15 | | t-2(3w-2t)=2t+9 | | 8y=-64x+16 | | 5(3w-2)-7=23 | | x-x*0.2765=1200 | | 3(2z+1)=35 | | 7p^2=-36p-5 | | -2a+5+3a=14-21 | | x-x*0.2765=1000 |

Equations solver categories